Ubuntu : up and running - Nixon, Robin, 1961- (O'Reilly Media, 2010)
Ubuntu for everyone! This popular Linux-based operating system is perfect for people with little technical background. It's simple to install, and easy to use -- with a strong focus on security. Ubuntu: Up and Running shows you the ins and outs of this system with a complete hands-on tour. You'll learn how Ubuntu works, how to quickly configure and maintain Ubuntu 10.04, and how to use this unique operating system for networking, business, and home entertainment.